"Design of novel WO3/CB nanohybrids" An affordable and efficient electrochemical sensor for the detection of multifunctional flavonoid rutin. Issue 5 (21st March 2018) - Kubendhiran, Subbiramaniyan; Sakthivel, Rajalakshmi; Chen, Shen-Ming; Yeah, Qin-Jin; Mutharani, Bhuvanenthiran; Thirumalraj, Balamurugan
Abstract : A CB/WO3 nanohybrid-modified SPCE was applied for the electrochemical determination of rutin. Abstract : The multifunctional properties of rutin have been utilized in the preparation of various pharmaceutical products. As a result, rutin is considered to be one of the most consumed flavonoid substances in pharmaceutical applications. Hence, researchers have been devoted to developing a simple, cheap and highly efficient electrochemical sensor for the detection of rutin. Nowadays, inorganic nanomaterials, especially metal oxides, with distinct structures and properties are being used for the development of various kinds of electrochemical sensors. The wide band gap values of WO3 make it a potentially important sensing material. Therefore, we have synthesized novel CB/WO3 nanohybrids using a single step hydrothermal technique and applied them for the electrochemical detection of rutin. In this work, we have chosen the inexpensive and superconductive CB for the synthesis of the nanohybrids, which is an alternative to other carbonaceous materials. The structural, morphological and compositional properties of the synthesized material were systematically characterized by various suitable spectrophotometric techniques. Moreover, the as-prepared electrode materials exhibited a good electrochemical performance towards the electro-oxidation of rutin. Fascinatingly, the lowest LOD of about 2 nM with appreciable linearity from 0.01 to 75.46 μM was obtained for the electrochemical determination of rutin. Furthermore, the practical feasibility of the proposed sensor was investigated using commercially available rutin-containing tablets.